Winter harbour, Melville Island, Arctic Sea, 1909 : Voyage of C.G.S. "Arctic," 1908-1909, J.E. Bernier, Commander / E.M. Longtin, Nov. 9 - E. M. Longtin cartographer (Great Britain. Hydrographic Office, 1910)
Is part of: Bernier. J. E. Report on the expedition to the Arctic Island. Ottawa : Hydrographic Office, 1910. Contents/Summary: Chart of Melville Island. depths shown by soundings. Notes: Includes legend.; Relief shown by hachures, form lines and spot heights.; From Bernier's Report on the expedition to the Arctic island. Ottawa : Hydrographic Office, 1910.; "Report on the Dominion of Canada Govt. Expedition to the Arctic Islands and Hudson Strait on oard the D.G.S. "Arctic" by Capt. J.E. Bernier, Ottawa, 1910." -- label affixed in top margin. Color 1:30,000